Reforestation Achievement Monitoring at Mining Area through Soil Index Model - Nining Puspaningsih; Kukuh Murtilaksono; Naik Sinukaban; I Nengah Surati Jaya; Yadi Setiadi (Jurnal Manajemen Hutan Tropika, 2010)
The achievement of the reforestation is expected to reach a climax forest ecosystem. The objectives of this studywas to develop soil index model on monitoring of reforestation achievement. The study used a statistical approach to obtain soil index model to determine the achievement level of reforestation in mining area. The achievement indices for each variable were derived from the best regression model developed, while the weights of eachvariable were computed based on magnitude of regression coefficient for each indicator. The level of reforestationachievement index was initially developed by the use of 4 indicators, i.e. physical soil, biological soil, chemical soil, and litter index. Of those indicators, the study revealed that the heights weight for reforestation monitoring was chemical soil, which is composed pH, cation exchange capacity (CEC), macro-micro nutrient, and base saturation.